Relationship of Anxiety and Depression with Surgical Resection of Meningioma: a Systematic Review - Silvia Martins Fernández (2020)
Objective Despite its benign nature, meningiomas are associated with several mental disorders. The incidence and nature of psychiatric symptoms depends on the location of the tumour, its volume and the surrounding oedema. Neuropsychological comorbidities are common and meningiomas, over other types of brain tumours, cause high levels of anxiety and depression. Current standard of care consists of neurosurgical resection of the tumour. With this systematic review, we aim to better understand the variation of anxiety and depression before and after surgical resection of meningiomas, in order to improve patient care. Methods A Systematic research of literature was performed, in three different databases, MEDLINE, Web of Science and SCOPUS, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. To be included in the review, articles had to contemplate presurgical and postsurgical evaluation of anxiety and depression in meningioma patients. Case reports, reviews, meta-analyses and editorial letters were excluded. Results From the 611 articles retrieved, 13 were selected to perform the qualitative analysis. Overall, 1259 patients were included. The papers included in the review were observational, long term, prospective studies. Assessment of anxiety, overall, revealed declining values during the entire follow-up. Results also showed lower depression scores at the first postsurgical evaluation. However, studies with two postsurgical assessments revealed increasing levels of depression at the second evaluation. Conclusion Anxiety and depression are frequent in patients with meningioma but seem to decrease after meningioma resection. The present review revealed several methodological discrepancies in the studies analysed, therefore conclusions cannot be made with certainty, and more accurate investigational methods are needed in this field.